2005
DOI: 10.1111/j.1365-2796.2005.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin reflects severity of liver disease but not insulin sensitivity in liver cirrhosis

Abstract: . Background.  The adipocytokine adiponectin has been proposed to play important roles in the regulation of energy homeostasis, insulin sensitivity and shows anti‐inflammatory properties. Aim.  In this study we investigated the role of circulating adiponectin in different chronic liver diseases, its regulation by systemic anti‐tumour necrosis factor (TNF)‐α treatment and its hepatic metabolism. Patients and methods.  Plasma adiponectin levels were determined in 87 patients with liver cirrhosis of different aet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 41 publications
9
67
1
3
Order By: Relevance
“…To our knowledge, only few studies examined the role of adiponectin in patients with chronic HBV infection [28,29,31]. We have examined the change of serum adiponectin levels before and after interferon a therapy in 10 patients with chronic HBV infection and found that the adiponectin levels did not correlate with the response to interferon therapy (responders versus nonresponders: 17.7 ± 4.1 vs. 9.2 ± 1.0 lg/ml, P = 0.10) [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, only few studies examined the role of adiponectin in patients with chronic HBV infection [28,29,31]. We have examined the change of serum adiponectin levels before and after interferon a therapy in 10 patients with chronic HBV infection and found that the adiponectin levels did not correlate with the response to interferon therapy (responders versus nonresponders: 17.7 ± 4.1 vs. 9.2 ± 1.0 lg/ml, P = 0.10) [31].…”
Section: Discussionmentioning
confidence: 99%
“…These results contradict previous concept of the inverse relationship between degree of insulin resistance and adiponectin levels and prompted us to conduct further studies. Kaser et al [29] evaluated serum adiponectin level in 87 patients with cirrhosis of different etiologies, including HBV-related cirrhosis (n = 8) and 21 healthy controls. They found that serum adiponectin level increased in patients with cirrhosis independent of the etiology of liver disease [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cross-sectional studies showed the opposite results of significantly elevated circulating adiponectin levels in cirrhosis patients of different etiologies when compared with healthy controls (23,24). Furthermore, adiponectin was found to be significantly higher in patients with more advanced chronic liver disease, leading to the speculation that adiponectin might be an indicator of liver disease severity (24).…”
Section: Introductionmentioning
confidence: 99%